Species diversity, virulence, and antimicrobial resistance of the nasal staphylococcal and mammaliicoccal biota of reindeer - Jolanta Kochel-Karakulska; Marta Maślanko; Marta Woroszyło; Małgorzata Szewczuk; Bartłomiej Grygorcewicz; Karol Fijałkowski (BMC Veterinary Research)
Abstract Background Staphylococcus (S.) spp. and Mammaliicoccus (M.) spp., in addition to their established role as components of the human and animal microbiota, can also cause opportunistic infections. This study aimed to characterize bacteria recovered from nasal cavities of healthy adult reindeer from two farms located in Poland (15 reindeer) and Germany (15 reindeer). The research include bacteria isolation, species identification, detection of selected superantigen (SAg) genes, assessment of biofilm-forming capability in vitro, and evaluation of antimicrobial resistance. Results Seventy-four staphylococci and mammaliicocci from 14 different species were isolated from 30 nasal swabs, with one to four strains obtained from each reindeer. The most frequently identified species was S. equorum, followed by S. succinus, M. sciuri, S. xylosus, M. lentus, S. chromogenes, S. devriesei, M. vitulinus, S. auricularis, S. agnetis, S. edaphicus, S. petrasii, S. simulans, and S. warneri. A greater species diversity was observed among the reindeer from Poland compared to those from Germany. All isolated bacteria were coagulase negative and clumping factor negative and did not carry any of the 21 analyzed SAg genes. M. sciuri demonstrated the highest antimicrobial resistance (100%), followed by S. succinus (91%) and S. equorum (78%). Resistance to rifampicin was the most common (30% strains). Sixteen strains (22%) exhibited biofilm production at least 10% greater than the strong biofilm-forming S. aureus ATCC 6538. Conclusions This study reveals a significant knowledge gap regarding the nasal microbiota of reindeer. It contributes to our understanding of staphylococcal and mammaliicoccal biota of reindeer and underscores the necessity for monitoring of microbial populations to assess their health implications for both animals and humans, particularly concerning the zoonotic transmission of bacteria.